2019
DOI: 10.23887/jpdi.v1i2.2681
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Sains Teknologi Masyarakat Terhadap Hasil Belajar Ipa Ditinjau Dari Literasi Digital Siswa Kelas v Sekolah Dasar Gugus Vi Kecamatan Mengwi

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran STM terhadap hasil belajar IPA ditinjau dari literasi digital siswa kelas V sekolah dasar Gugus VI Kecamatan Mengwi. Penelitian ini merupakan kuasi eksperimen dengan rancangan faktorial 2 x 2. Data dikumpulkan dengan menggunakan metode tes. Data yang dikumpulkan adalah  hasil belajar dan literasi digital. Data dianalisis menggunakan anava dua jalur. Sampel penelitian sebanyak 100 siswa SD di Gugus VI Kecamatan Mengwi. Hasil penelitian ini me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The results of research that take the theme of digital literacy have been carried out by several researchers, including research on increasing digital literacy that can be done using the Technology-Embedded Scientific Inquiry (TESI) Learning Model (Nurcahyo, 2016). In addition, there is also research that uses the Science Technology Society learning model to determine (Jayanti, 2019) Science literacy can be trained using Schoology-based e-learning (Misbah et al, 2018). The use of website-based learning media can also improve students' digital literacy skills in learning physics (Rahayu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of research that take the theme of digital literacy have been carried out by several researchers, including research on increasing digital literacy that can be done using the Technology-Embedded Scientific Inquiry (TESI) Learning Model (Nurcahyo, 2016). In addition, there is also research that uses the Science Technology Society learning model to determine (Jayanti, 2019) Science literacy can be trained using Schoology-based e-learning (Misbah et al, 2018). The use of website-based learning media can also improve students' digital literacy skills in learning physics (Rahayu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The results of research that take the theme of digital literacy have been carried out by several researchers, including research on increasing digital literacy that can be done using the Technology-Embedded Scientific Inquiry (TESI) Learning Model (Nurcahyo, 2016). In addition, there are also studies that use the Science Technology Society learning model to determine its effect on science learning outcomes in terms of digital literacy (Jayanti et al, 2019). Science literacy can be trained using Schoology-based e-learning (Misbah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Kemampuan metakognitif ini adalah sangat penting bagi siswa karena Siswa mampu menyadari apa yang harus dilakukan Dan yang menjadi kesalahan JJPGSD P-ISSN: 2614-4727 E-ISSN: 2614-4735 sehingga siswa mampu untuk mengevaluasi kesalahan tersebut. Strategi pembelajaran yang sesuai efektif untuk kegiatan pembelajaran yang menekankan pada keaktifan siswa (Jayanti et al, 2017;Kimianti & Prasetyo, 2019).…”
Section: Pembahasanunclassified
“…The tendency of students to obtain information through speech is still the main thing rather than through reading. Based on the results of international research, it was also found that the literacy skills of Indonesian students are still relatively low (Jayanti et al, 2017;Pertiwi et al, 2018). The findings of research conducted by PIRLS also state that the ability of elementary school students to read, Indonesia ranks 45th out of 48 countries (Hidayat, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%